Effects of intra-class peer mentorship intervention programme on the academic performances of academically underperforming medical students in Nigeria - George Uchenna Eleje; David Chibuike Ikwuka; Kingsley Chinaza Nwosu; Lydia Ijeoma Eleje; Obiageli Ifeoma Ikwuka; Nasiru Sani; Jean Paul Niyoyita; Kazeem Bidemi Okesina; Uchechukwu Dimkpa; Uchechukwu Kevin Nwanna; Victor Bassey Archibong; Eric Twizeyimana; et al. (BMC Medical Education)
Abstract Background A significant gap exists in understanding the effectiveness of intra-class (same-class) level peer mentorship programmes designed to enhance academic performance, well-being, and student involvement among underperforming medical students. This study assessed the effectiveness of intra-class (same-class) peer mentorship programme on the academic performances, subjective well-being and school engagement of academically underperforming medical students in Nigeria. Methods This was a quasi-experimental research consisting of the pretest-posttest control design at Nnamdi Azikiwe University, Awka, Nigeria. Preclinical medical students from same class level were categorised into three groups: 7 academically underperforming students (mentees) scoring below 45% on the continuous assessment test (CAT), 12 mentors scoring 70% or above, and 30 controls scoring between 50% and 70%. Participants completed the Subjective Vitality Scale (SVS) and the self-University Student Engagement Inventory (USEI) before and after the 6-month programme, led by an experienced educationist. A post-programme CAT assessed academic performance, and quantitative data were analysed using paired-samples t-tests to evaluate changes in academic performance, SVS and USEI. The dimensions of students’ subjective vitality and the school engagement were considered in the analysis. Results A total of 49 students were included in the study, with 7 (14.3%) in the mentee group, 12 (24.3%) in the mentor group and 30 (61.2%) in the control group. The same-class peer mentorship intervention led to a significant improvement in CAT scores for the mentee group, with their median score rising from 40.0 to 70.0% (p = 0.003), while the control group’s median slightly decreased. The mentee group’s SVS (p = 0.722) and USEI (p = 0.388) scores non-significantly improved post-intervention. However, specific USEI items revealed significant post-intervention improvements in mentees’ classroom engagement or increased participation in discussions (p = 0.001) and enjoyment of school (p = 0.031). SVS items showed non-significant differences between groups post-intervention. Conclusion The same-class peer mentorship intervention significantly improved CAT scores among academically underperforming medical students, with modest gains in SVS and USEI scores. While overall vitality and engagement changes were not significant, classroom engagement improved. These findings support intra-class peer mentorship in medical education.